2014
DOI: 10.1111/isj.12042
|View full text |Cite
|
Sign up to set email alerts
|

Technostress: negative effect on performance and possible mitigations

Abstract: We investigate the effect of conditions that create technostress, on technology-enabled innovation, technology-enabled performance and overall performance. We further look at the role of technology self-efficacy, organizational mechanisms that inhibit technostress and technology competence as possible mitigations to the effects of technostress creators. Our findings show a negative association between technostress creators and performance. We find that, while traditional effort-based mechanisms such as buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
528
5
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 459 publications
(577 citation statements)
references
References 105 publications
20
528
5
24
Order By: Relevance
“…Another study found that the brain scans of 17 subjects addicted to the Internet resembled those of cocaine addicts (Lin et al, 2012). In fact, Tarafdar et al (2015) surveyed 3,100 organizational employees and found that, of the employees who reported feeling stressed by technology at work, 46 percent exhibited medium to high addictive symptoms to the same technology that "stresses them out".…”
Section: Stress and Addictionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study found that the brain scans of 17 subjects addicted to the Internet resembled those of cocaine addicts (Lin et al, 2012). In fact, Tarafdar et al (2015) surveyed 3,100 organizational employees and found that, of the employees who reported feeling stressed by technology at work, 46 percent exhibited medium to high addictive symptoms to the same technology that "stresses them out".…”
Section: Stress and Addictionmentioning
confidence: 99%
“…Following this line of reasoning, the strain, or the outcome of stress, is the susceptibility to Internet addiction. Thus, individuals who experience social media-induced technostress are likely to have addiction-like symptoms (Tarafdar et al, 2015).…”
Section: Social Media Technostress Dct and Addictionmentioning
confidence: 99%
See 3 more Smart Citations